Pengaruh Skeptisme Profesional Dan Etika Profesi Terhadap Pendeteksi Kecurangan (Survei Pada Kantor Akuntan Publik di Kota Bandung) (Jurnal Riset Akuntansi, 2023)
This study aims to determine how much influence Professional Skepticism and Professional Ethics have on Fraud Detection in 13 Public Accounting Firms in Bandung. The method used in this research is descriptive and verification method with a quantitative approach. The data source used is primary data with data collection techniques carried out by survey methods through questionnaires to 40 auditors at 13 Public Accounting Firms in Bandung. The data analysis method used in this research is multiple linear regression analysis which is tested using SPSS 23.0 for Windows software. The results of this study indicate that Professional Skepticism and Professional Ethics have an effect on Fraud Detection. Keywords: Professional Skepticism, Professional Ethics, and Fraud Detection